Empowering Waqf to Enhance Sustainable Social Welfare in Indonesia: A Systematic Literature Review from the Perspective of Maqasid Shariah - Deliar Agha Firdaus; Tutik Hamidah; Aunur Rofiq; Royyan Ramdhani Djayusman; Bima Fandi Asy’ari; Shehla Riaz; Safa Alrumayh (Universitas Muhammadiyah Surakarta, 2026)
Objective: This study aims to identify the contribution of waqf empowerment to improve social welfare, which is then analyzed from the perspective of maqashid sharia. Theoretical framework: The theoretical framework of this research uses the framework of maqashid sharia as a normative basis to assess the role of waqf as an Islamic socio-economic instrument that is oriented towards benefits. Literatur review: Previous studies have generally discussed waqf as an instrument of Islamic philanthropy, but systematic analysis of the contribution of waqf empowerment to social welfare based on maqashid sharia is still limited. Methods: The method used is a systematic literature review (SLR) with a study period year (2016-2025), which resulted in 22 relevant articles. Result: The results of this study show that waqf empowerment contributes to improving social welfare, including First, the economy (poverty alleviation, funding economic activities including agriculture, MSMEs, and entrepreneurship training). Second, education (expanding students' access to learning, creating equal distribution of education, funding scientific research, and tahfidz to strengthen Qur'anic literacy). Third, health (logistical assistance for medical personnel, funding medical research and the development of modern health infrastructure). Fourth, the environment (protecting forest areas, maintaining the ecological function of the land, clean water management, and the development of alternative energy based on solar and biomass). Then in the five Islamic principles of maqashid sharia, including hifz al-mal and hifz al-nafs in the economic category, hifz al-'aql and hifz al-nasl in the category of education, hifz al-nafs in the health sector, hifz al-mal and hifz al-nasl in the environmental category. Implications: These findings provide a conceptual basis for the development of productive waqf policies oriented towards social welfare based on maqasid sharia. Novelty: This study offers a systematic mapping of the contribution of waqf empowerment based on maqasid sharia which enriches Islamic economic and philanthropic literature.